Development of Geothermal Potential Resources Map using Land Surface Temperature from MODIS in Northern Thailand - Sainarmtip, Rutaichanok; Wetchayont, Parichat; Chenrai, Piyaphong (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2020)
Geothermal energy is heat energy within the earth’s interior that can be developed to produce electricity continuously. In many countries, remote sensing technology is applied to explore geothermal energy sources. Using the thermal infrared satellite data and associated with other data estimated and analyzed the land surface temperature for assessing the area of initial geothermal potential. In this study, Land Surface Temperature (LST) data from MODIS satellite is analyzed with rock and fault data, which are analyzed geothermal potential using the weighted overlay analysis technique in Northern Thailand. The results of the statistical analysis, the Pearson correlation between variables shown that the rock types was most closely related to the hot water temperature at the surface (0.587), distance from faults (-0.410), and land surface temperature anomaly (-0.376), respectively. The geothermal potential map was classified into 3 levels as follows high, moderate and low were 12.29, 36.32 and 51.39 %, respectively. The accuracy between the position and temperature level of the hot springs that appear in the area and the geothermal potential level obtained from the study found that 53.3 % accuracy, which classified as a moderate level.